Pengaruh Kombinasi Tens dan Eccentric Exercise Terhadap Penurunan Nyeri pada Pasien Tennis Elbow di RS Citra Sari Husada Karawang - Aprilia, Mia; Sartoyo, Sartoyo; Ansyori, Anis; Hargiani, Fransisca Xaveria (Dinasti Research, 2025)
Tennis elbow (lateral epicondylitis) is a feeling of pain on the outside of the elbow related to excessive extension of the hand. The main causes are repetitive overuse of muscles, and heavy manual labor increases the risk of developing Tennis elbow. The problem that often arises in cases of tennis elbow is a decrease or functional limitation in work, sports and daily activities. This is caused by pain caused by the inflammatory process that occurs in the lateral epycondyle. Tennis elbow cases can be given physiotherapy intervention in the form of TENS and Eccentric Exercise. This study aims to determine whether there is an effect of the combination of TENS and Eccentric Exercise on pain in Tennis elbow patients at Citra Sari Husada Hospital Karawang.This research is pre-experimental research. The research design refers to one group pretest-posttest. The population is tennis elbow patients at Citra Sari Husada Hospital Karawang. The population in this study was all patients who came with complaints of tennis elbow pain to the medical rehabilitation installation. The sample is part of or representative of the target population. The samples in the study were tennis elbow sufferers at the medical rehabilitation installation at Citra Sari Husada Hospital in Karawang who met the inclusion and exclusion criteria, totaling 30 samples.Primary data was collected through direct interviews followed by examination. Data analysis used the Wilcoxon test. The results of the research show that based on the analysis, it is known the effect of the combination of TENS and Eccentric Exercise on pain in Tennis elbow patients at Citra Sari Husada Hospital, Karawang. Based on the research results, it is recommended that future researchers conduct research with a larger sample.